2005
DOI: 10.1110/ps.051501605
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure and substrate specificity of the β‐ketoacyl‐acyl carrier protein synthase III (FabH) from Staphylococcus aureus

Abstract: b-Ketoacyl-ACP synthase III (FabH), an essential enzyme for bacterial viability, catalyzes the initiation of fatty acid elongation by condensing malonyl-ACP with acetyl-CoA. We have determined the crystal structure of FabH from Staphylococcus aureus, a Gram-positive human pathogen, to 2 Å resolution. Although the overall structure of S. aureus FabH is similar to that of Escherichia coli FabH, the primer binding pocket in S. aureus FabH is significantly larger than that present in E. coli FabH. The structural d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
90
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(98 citation statements)
references
References 31 publications
(48 reference statements)
8
90
0
Order By: Relevance
“…8A). The FAS initiation activity of PA5174 is on par with E. coli FabH and with previously reported data (13,63).…”
Section: Fig 2 Fatty Acid ␤-Ketoacyl Acyl Carrier Protein (Acp) Synthsupporting
confidence: 92%
See 1 more Smart Citation
“…8A). The FAS initiation activity of PA5174 is on par with E. coli FabH and with previously reported data (13,63).…”
Section: Fig 2 Fatty Acid ␤-Ketoacyl Acyl Carrier Protein (Acp) Synthsupporting
confidence: 92%
“…8A). The FAS initiation activity of PA5174 is on par with E. coli FabH and with previously reported data (13,63).We next examined the reaction product of PA5174 using conformation-sensitive urea-PAGE with [2-14 C]malonyl-ACP (68). The putative ␤-acetoacetyl-ACP product of PA5714 migrates faster than the starting substrate [2-…”
supporting
confidence: 73%
“…A total of 235 of these KS contigs encoded uninterrupted protein sequences of at least 150 amino acids; these results demonstrated that the quality of the data was high and sufficient for further phylogenetic analysis. These contigs also revealed the presence of conserved cysteine and histidine residues in the catalytic triad (CHH) of active KS domains from type I PKSs (38,39) as well as the primer-attaching conserved motifs DPQQR and HGTGT (40, 41) (see Fig. S2 in the supplemental material).…”
Section: Resultsmentioning
confidence: 99%
“…The energy minimization was carried out by MM2 and finally by RHF/3-21G. Automated docking was used to determine the orientation of inhibitors bound in the active site of bacterial beta-ketoacyl-acyl carrier protein synthase III (FabH; pdb id:3IL7) [29,38]. An incremental construction algorithm method, implemented in the program FlexX embedded LeadIT, was employed.…”
Section: Molecular Dockingmentioning
confidence: 99%
“…Molecular docking studies were also carried out to understand the binding pattern and to support in vitro antimicrobial data of synthesized most active compound [27,28]. Automated docking technique was used to determine the orientation of inhibitors, bound in the active site of β-ketoacyl-acyl carrier protein synthase III (FabH; pdb id:3IL7) [29]. β-ketoacyl-acyl carrier protein synthase encoded by the fabH gene is reported to catalyze the first : 3076.56 (C-H str., alkenes), 2928.04 (C-H str., aliphatic), 1741.78 (C=O str.…”
Section: Introductionmentioning
confidence: 99%